Tourist Satisfaction in Mediating the Influence of Tourist Attractions and Facilities on the Intention to Revisit Waduk Darma, Kuningan Regency (6945) - Sembiring, Vienna Artina; Ingkadijaya, Rahmat; Nurbaeti, Nurbaeti; Rahmanita, Myrza (Jurnal Penelitian Pariwisata, 2024)
The research aims to determine tourists' satisfaction in mediating the influence of tourist attractions and facilities on their interest in revisiting Waduk Darma, a breathtaking natural dam in Kuningan Regency. This study uses a quantitative approach. The population of this study is tourists who visit Waduk Darma. Sampling was done using the Accidental Sampling technique, and data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) program. The results of this study are as follows: tourist attractions have a positive and significant influence on tourists' satisfaction, facilities have a positive and significant influence on tourists' satisfaction, tourists' satisfaction has a positive and significant influence on their interest in revisiting, tourist attractions have a positive and significant indirect influence on their interest in revisiting through tourists' satisfaction with significant values, facilities have a positive and significant indirect influence on their interest in revisiting through tourists' satisfaction. To increase the level of tourist visits, the Kuningan local government is expected to improve facilities and tourist attractions that can increase tourists' satisfaction. Keywords: tourist attractions, facilities, tourist satisfaction, intention to revisit